Stress dan Kesehatan Mental di Masa Pandemi COVID-19 - Yelvi Levani; Uswatun Hasanah; Nur Fatwakiningsih (PROCEEDING UMSURABAYA, 2020)
AbstractCOVID-19 (Corona Virus Infection Disease 2019) is a respiratory tract infection caused bythe novel coronavirus. The disease has spread throughout the world, causing a pandemic. Thiscondition affects all aspects of life, including social and economic. Uncertainty in all aspectsof life can cause stress. This stressful condition can affect the mental health of an individual sothat it affects their daily activities. Stress can impaired immunity as well as anxiety disordersand depression. Good stress management and prevention are needed in these circumstances toreduce the impact of stress on everyday life. Therefore, this literature review aimed to discussthe effect of stress on mental health during the COVID-19 pandemic.Keywords: COVID-19, mental health, stress